Prenatal diagnosis of fetomaternal hemorrhage by a novel hydrogel fluoroimmunoassay that accurately quantifies fetal haemoglobin - Li, Xinyang; Yin, Moli; Wang, Hongmei; Duan, Shengbao; Wang, Huiyan; Li, Yong; Liu, Tiemei (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Fetomaternal hemorrhage (FMH) is an alloimmunization resulting caused by the incompatibility between fetal and maternal blood. For the prevention of newborn haemolytic disease (HDN), it is crucial to quantify the amount of fetomaternal hemorrhage. However, the classical Kleihauer–Betke test (K-B test) for detecting fetomaternal hemorrhage is limited by experimental tools and conditions and is not suitable for routine clinical use. Consequently, the method of prenatal diagnosis of fetomaternal hemorrhage applicable to the clinic is a topic worthy of further study. Therefore, it is worthwhile to further investigation on the clinically applicable prenatal diagnosis method for fetomaternal hemorrhage. Methods: This experiment demonstrates hydrogel’s ability to separate sensitized red blood cells from soluble antibodies. Using flow cytometry the fluorescence values of sensitized red blood cells and fluorophore-labeled antibodies were measured, and the testing steps for the detection products of a novel technology were determined. The properties of a hydrogel fluoroimmunoassay were evaluated by distinguishing between the amounts of fetal and adult haemoglobin. The precision of this technology is evaluated using the Kleihauer–Betke test as a comparison. Results: This experiment compared the detection of haemoglobin fluorescence in adults (n = 2) and fetuses (n = 6). At the same time, the fluorescence intensity of different fetal haemoglobin (HbF) in adult haemoglobin (HbA) was calculated. The fluorescence value is 1.6% when the fetal hemoglobin concentration is 0.1%. Conclusion: The novel hydrogel fluoroimmunoassay can accurately determine the fluorescence intensity by flow cytometry to differentiate fetal haemoglobin from adult haemoglobin, quantitatively prenatally diagnose fetal haemoglobin, address the incompatibility between fetal and maternal blood types, and prevent alloimmunization.